A identidade profissional do professor de Matemática frente ao trabalho docente no ensino fundamental em ciclos - Zanini, Renato (2006)
The current existence of a school in conflict, that operates at the same time in coherency with the premises of a serial organization, and in coherency with the premises of a cyclic organization, directed the interest of this research, that is to investigate how the Mathematics teachers understand and incorporate their work in classrooms organized in cycles, focusing the teaching professional identity, having the objective, therefore, to highlight some elements of practice that are influencing the professional identity building for these teachers. With that aim in mind, this documented inquiry on the trajectory of the cycles in the country was done, also deep diving on the principles of the Continued Progression regimen that divides basic education in cycles and is valid since the year of 1998 in Sao Paulo state public schools. The field research encompassed ten public schools in the country side of Sao Paulo state, through the application of a questionnaire and interviews with Mathematics teachers acting during the year of 2005 in basic education classrooms (mixing rooms of cycle recovery, mixed classrooms, and basic education classrooms in general). In order to meet the expectations of the inquiry, a study on "teaching professional identity" was also performed and, based on different approaches, in this research it gained a particular meaning, being used as one of the theoretical axis for the research, since the focus of the inquiry is the construction of the professional identity of Mathematics teachers when working in classrooms organized in cycles. Through the analysis and interpretation of all the information cited above, it can be said that some elements of the practice in teachers' working lives in the education organized by cycles deeply and strongly modify the meaning that each teacher has of its teaching work, causing permanent conflicts that influence the building of the professional identity of these teachers